Development of an implementation plan for the 6-PACK falls prevention programme as part of a randomised controlled trial: Protocol for a series of preimplementation studies - Barker, A.; Morello, R.; Ayton, D.; Hill, Keith; Landgren, F.; Brand, C. (BMJ Publishing Group, 2016)
Background: Inhospital falls cause morbidity, staff burden and increased healthcare costs. It is unclear if the persistent problem of inhospital falls is due to the use of ineffective interventions or their suboptimal implementation. The 6-PACK programme appears to reduce fall injuries and a randomised controlled trial (RCT) was undertaken to confirm effects. This paper describes the protocol for the preimplementation studies that aimed to identify moderators of the effective use of the 6-PACK programme to inform the development of an implementation plan to be applied in the RCT. Methods: The 6-PACK project included five preimplementation studies: (1) a profile of safety climate; (2) review of current falls prevention practice; (3) epidemiology of inhospital falls; (4) acceptability of the 6-PACK programme; and (5) barriers and enablers to implementation of the 6-PACK programme. The Theoretical Domain Framework that includes 12 behaviour change domains informed the design of these studies that involved 540 staff and 8877 patients from 24 wards from six Australian hospitals. Qualitative and quantitative methods were applied with data collected via: structured bedside observation; daily nurse unit manager verbal report of falls; audit of medical records, incident reporting and hospital administrative data; surveys of ward nurses; focus groups with ward nurses; and key informant interviews with senior staff. Discussion: Information on contextual, system, intervention, patient and provider level factors is critical to the development of an implementation plan. Information gained from these studies was used to develop a plan applied in the RCT that addressed the barriers and harnessed enablers.